COMPARISON OF LEGAL SYSTEMS IN THE PERSPECTIVE OF CONTEMPORARY ISSUES AND THEIR APPLICATION IN INDONESIA - Rahardja, Satria Dwie; Hoesein, Zainal Arifin (Ridwan Institute, 2024)
This study aims to explore how the Indonesian legal system can adapt to contemporary issues through comparative analysis with legal systems in other countries. The study first uses secondary data collection methods and case studies to identify the differences and similarities between Indonesia's legal system and the common law and civil law legal systems. The results of this analysis are expected to not only provide insight into the best practices that can be adopted by Indonesia to be able to increase the effectiveness of law enforcement in the face of modern challenges, but also offer a solid foundation for reforming legal policies to be more responsive and adaptive to the challenges of digitalization and globalization.